Correlates of Internationalization of Higher Education Institutions in the Philippines - Narbarte, Miriam P.; Chan, Judith Mary Ann (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Internationalization is currently the priority of higher education institutions (HEIs) in the Philippines and in many countries worldwide. Internationalization contributes to the development of the academic programs of HEIs. This research aimed to determine the factors that influence the internationalization of HEIs in the Philippines. The articulated institutional commitment, administrative structure and staffing, curriculum and learning outcomes, faculty policies and practices, student mobility, and collaboration partnerships were the predictor variables and internationalization as a criterion variable. An online survey questionnaire was used to gather the information that addressed the objectives of the study and was distributed to the HEIs in the Philippines. Three hundred forty-three faculty from 97 HEIs answered the questionnaires. The respondents were from autonomous (25.4%), deregulated (11.7%), and regulated (63%) HEIs. The articulated institutional commitment, administrative structure and staffing, curriculum and learning outcomes, faculty policies and practices, student mobility, and collaboration partnerships were highly evident and were found to be significantly correlated to the implementation of internationalization of HEIs in the Philippines. The results further revealed a moderate implementation of internationalization among HEIs in the Philippines. The regression analysis revealed that faculty policies and practices were the sole predictors of internationalization, with 18% variance accounted for. Having standard policies and guidelines, creating an internationalization awareness program, and administrative support are some recommendations based on the results to strengthen the internationalization programs of HEIs in the Philippines. Keywords : internationalization, higher education institutions (HEIs), faculty policies and practices